Investigação da rentabilidade de clientes: um estudo no setor hoteleiro do Nordeste - Leitão, Carla Renata Silva (2002)
This study presents an investigation about customer profitability in the hotel industry. It exposes the hotel industry´s history and its managerial environment, besides its importance to the society and economy, considering the increasement of the hotel industry. It realizes a literature survey about the customer profitability, emphasizing the informations that are necessary to measurement. In order to perceive the hotel reality, a questionnaire was applied in some hotels classified as middle and great size. It has covered five Brasilian Northeast states. The objective of the research is to investigate the existence of an individual measurement to the customer profitability, through the hotel´s information systems. The results reveal that 81,6% of the sampled hotels do not evaluate the individual profitability obtained with the customers , while 18,4% do it. Although, 85,8% recognize the importance of the electronic system that supplies this information for decisions. Finally, it concludes that the informations about individual customer profitability may provide a good opportunity to the hotel maximize your customer relationships